2018
DOI: 10.1016/s1470-2045(18)30254-7
|View full text |Cite
|
Sign up to set email alerts
|

MAGE-A3 immunotherapeutic as adjuvant therapy for patients with resected, MAGE-A3-positive, stage III melanoma (DERMA): a double-blind, randomised, placebo-controlled, phase 3 trial

Abstract: GlaxoSmithKline Biologicals SA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
91
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(92 citation statements)
references
References 29 publications
0
91
0
1
Order By: Relevance
“…Therefore, its further development for use in NSLCs has been stopped (Vansteenkiste et al, 2016). Similar conclusions were drawn from a phase III trial of a MAGE-A3/AS015 vaccine in patients with resected, MAGE-A3-positive, stage III melanoma, which led to the arrest of the clinical development of this vaccine for use in melanoma (Dreno et al, 2018).…”
Section: Therapeutic Vaccines Cancermentioning
confidence: 83%
“…Therefore, its further development for use in NSLCs has been stopped (Vansteenkiste et al, 2016). Similar conclusions were drawn from a phase III trial of a MAGE-A3/AS015 vaccine in patients with resected, MAGE-A3-positive, stage III melanoma, which led to the arrest of the clinical development of this vaccine for use in melanoma (Dreno et al, 2018).…”
Section: Therapeutic Vaccines Cancermentioning
confidence: 83%
“…Other methods of immunotherapy (e.g. interleukin 2), vaccinations or cytotoxic medication do not have any application in post-operative adjuvant treatment [1,4,5,30].…”
Section: Discussionmentioning
confidence: 99%
“…CT genes were first observed and considered to be candidate targets for immunotherapy due to their immunogenicity. However, 19 of the 24 phase II/III clinical trials that tested 17 distinct therapeutic anticancer vaccines failed to achieve their primary objectives (20)(21)(22)(23); this included a trial for the vaccine targeting MAGEA3 in non-small cell lung cancer (NSCLC) and melanoma. A recent study reported that the aneuploidy level can predict the reduced level of cytotoxic infiltrating immune cells (8).…”
Section: Discussionmentioning
confidence: 99%